THE USE KASAR AND TENGA’AN OF MADURESE SPEECH LEVEL OF STUDENTS OF MADRASAH IBTIDAIAH MAMBAUL ULUM - Zainul Mustofa; Adi Sutrisno (JURNAL LITERASI, 2023)
This research focuses on the kasar and tenga’an speech level of the Madurese language used by students in 4th, 5th and 6th grades at the Madrasah Ibtidaiah Mambaul in Probolinggo Regency. This study aims to describe the use of the Coarse and Tenga'an speech levels in Madurese language among students at Madrasah Ibtidaiah Mambaul Ulum Probolinggo. This research is relevant to do because there is still a lack of research on linguistic phenomena in Probolinggo, especially in the field of local language pragmatics. Therefore, this research is not only relevant to do, but also important to do. Based on the analysis that the use of tengnga’an speech level is often used by students of Madrasah Ibtidaiah Mambaul Ulum Probolinggo in daily conservation. They use kasar level, because they have certain factors namely kinship (sibling), equality (classmate), and situation. Kasar level occur between 4th grade to 4th grade and 4th grade to 5th grade because they are classmates or they are brother and they are in informal situation. Tengnga’an level occur because first reasons is they want to give honor to their friend,and second because the senior wants to teach politeness to their junior. Tengnga’an level used by students of Madrasah Ibtidaiah Mambaul Ulum Probolinggo occur in informal situation when they are to give honor to their frien and because they live in are Madrasah Ibtidaiah Mambaul Ulum Probolinggo environment, so they have a good effect on their behaviour.